PENGEMBANGAN MEDIA VIDEO BERBASIS WAYGROUND MATA PELAJARAN IPAS MATERI ORGAN PERNAPASAN PADA SISWA KELAS 5 SDN DUKUH KUPANG V SURABAYA - Ramadamayanti, Risanda; Friendha Yuanta; Suprihatien (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning IPAS in elementary schools still faces challenges related to students’ difficulties in understanding abstract concepts, particularly in the topic of the human respiratory system. This condition is influenced by the limited use of interactive and technology-based learning media. This study aimed to develop a WayGroundbased instructional video and to determine its validity, feasibility, and effectiveness in IPAS learning for fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were fifth-grade students of SDN Dukuh Kupang V Surabaya. Data were collected through expert validation, student response questionnaires, and learning outcome tests using pre-test and post-test. The results showed that the WayGround-based instructional video achieved a high level of validity based on material and media expert assessments. The results of small-group, medium-group, and large-group trials indicated that students’ responses were categorized as very good. Furthermore, the effectiveness test revealed an improvement in students’ learning outcomes after using the developed media. Therefore, the WayGroundbased instructional video is considered valid, feasible, and effective for use in IPAS learning on the human respiratory system topic in elementary schools.